Symbolism in Frost’s Stopping by Woods on a Snowy Evening Perceived through Dayak Culture Perspective: A Post-Structuralism Approach - Nainggolan, Suli Angelina; Yulitriana, Yulitriana; Susanty, Susanty (The Study Program of English Education of Palangka Raya University, 2025)
This research aims to examine the symbolism in Frost’s Stopping by Woods on a Snowy Evening. It focuses on five symbols in the poem namely “woods”, “farmhouse”, “village”, “dark”, and “miles to go”. First, the symbols and the meanings are identified according to the previous studies. Second, the symbols and meanings are explored through the perspective of Dayak people in Kalimantan, Indonesia. They are then compared and analyzed. The method carried out is a qualitative approach based on the principles of Post-Structuralism. The result shows that the symbolisms in the poem are interpreted differently when they are perceived from a particular culture (Dayak culture). Previous studies mention that “woods”, for instance, symbolize beauty which can drag people away from their life purpose; while in Dayak culture, “woods” are sacred and should be protected. Therefore, the meaning of a literary work is open to cross-cultural interpretation which can provide a richer and meaningful experience for the readers. It is suggested that further studies can be conducted on how symbols in the poem are perceived in other cultures. It is possible that the symbols analyzed will be different from this study since each culture might have particular symbols that might not be found in other cultures.